PROGRESIVISME FILSAFAT PENDIDIKAN NEL NODDINGS DAN RELEVANSINYA DALAM HUBUNGAN GURU DAN MURID DI INDONESIA - , NUR HASAN ALI; , Dr. P. Hardono Hadi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to investigate Nel Nodding progressivism educational philosophy and its relevance in the relationship between teachers and students in Indonesia, this research tried to uncover the philosophy of progressivism in education Noddings that limited by five aspects, namely (1) the purpose of education (2) students and teachers (3) curriculum (4) ethics and moral (5) justice and democracy. Collection of hisoris factual is done by collecting data that relevant to the object of study in this research. The data are then systematized and analyzed using heurmeneutikheuristic approach. Nodding education philosophy progressivism view that the goal is always growing and evolving so Noddings concludes that the purpose of education is "continuing education" leading to "happiness", this goal rests on the principle of pragmatism-utilitarianism (happiness). Pupil is a dynamic figure who their wants and needs should be respected. Their wants and their needs have to be considered to determine the student learning objectives, the teaching methods, the subject matter, and the curriculum. Teachers serve as observator, facilitator, motivator and counselor. There is no such thing as a stiff curriculum in an ideal education, the curriculum must be tailored to the needs, interests, and talents of children. Children should early learners ethics, ethics education should be based on the balance of character education, imitation, and cognitive education. Ethical caring should be taught to children as part of community life. Whether male or female, rich or poor they deserve equal treatment in education. In democracy of education, every child deserves appreciated their voice and their choices. The relevance of âNoddings educational philosophy progressivismâ in the relationship between teachers and students is the students naturally appreciate and prepare students to reach the goal he had dreamed of, with full awareness, responsibility and moral integrity. Conclusion of this study that, Noddings progressivism educational philosophy is utilitarian-socialist progressivism, and teachers who understand the essence of progressive students will make children better able to achieve success in the future social life.